Atomic structure of Cs layer grown on Si(001)(2 x 1) surface at room temperature - Kim, JY; Park, JY; Seo, JH; Whang, CN; Kang, HJ; Kim, SS; Choi, DS; Chae, KH (ELSEVIER SCIENCE BV, 2003)
The atomic structure of Cs atoms adsorbed on the Si(0 0 1)(2 x 1) surface has been investigated by coaxial impact collision ion scattering spectroscopy. When 0.5 ML of Cs atoms are adsorbed on Si(0 0 1). at room temperature, it is found that Cs atoms occupy a single absorption site on T3 with a height of 3.18 +/- 0.05 Angstrom from the second layer of Si(0 0 1)(2 x 1) surface, and the bond length between Cs and the nearest Si atoms is 3.71 +/- 0.05 Angstrom. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: ENERGY ELECTRON-DIFFRACTION; PHOTOELECTRON DIFFRACTION; ION-SCATTERING; COVERAGE; SPECTROSCOPY; ADSORPTION; CESIUM; 2X1